1996
DOI: 10.1128/jb.178.21.6403-6406.1996
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and chemical characterization of a mutant that disrupts synthesis of the lipopolysaccharide core tetrasaccharide in Rhizobium leguminosarum

Abstract: A 2-kb region that complements the Tn5-derived lipopolysaccharide (LPS) rough mutant Rhizobium leguminosarum RU301 was sequenced. Two open reading frames (ORFs) were identified. The first ORF (lpcA) is homologous to a family of bacterial sugar transferases involved in LPS core tetrasaccharide biosynthesis. ORF2 (lpcB), in which Tn5 transposed, has no significant homology to any DNA in the GenBank-EMBL databases. Chemical characterization of LPS produced by strain RU301 demonstrated that the 3-deoxy-Dmanno-2-oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…lpcA was partially sequenced and was proposed to encode the galactosyltransferase because of its homology to other sugar transferases and chemical characterization of LPS isolated from an lpcA::Tn5 insertion mutant (24 -26). lpcB was sequenced entirely, and although it showed no homology to any known gene, it was proposed to encode the distal Kdo-transferase based upon the absence of the distal Kdo in the LPS core isolated from an lpcB transposon insertion mutant (24). We now demonstrate by means of our enzyme assays that lpcA does indeed encode the galactosyltransferase and that lpcB encodes the distal Kdo-transferase.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…lpcA was partially sequenced and was proposed to encode the galactosyltransferase because of its homology to other sugar transferases and chemical characterization of LPS isolated from an lpcA::Tn5 insertion mutant (24 -26). lpcB was sequenced entirely, and although it showed no homology to any known gene, it was proposed to encode the distal Kdo-transferase based upon the absence of the distal Kdo in the LPS core isolated from an lpcB transposon insertion mutant (24). We now demonstrate by means of our enzyme assays that lpcA does indeed encode the galactosyltransferase and that lpcB encodes the distal Kdo-transferase.…”
mentioning
confidence: 82%
“…X94963. The full-length lpcA gene shows moderate homology to many bacterial glycosyltransferase genes, including some of those involved in the assembly of LPS cores (2,4,24). For instance, the lpcA gene displays 30%, 27%, and 26% identity, respectively, to lgtC of Neisseria gonorrhoeae (45), to ipa-12d of Bacillus subtilis (46), and to rfaJ (waaJ) (2, 4) of E. coli.…”
Section: Sequential Addition Of Mannose Galactose and Kdo To The Acmentioning
confidence: 99%
See 1 more Smart Citation
“…viciae 3841. Several genes for production of extracellular EPSs have been identified in different strains and biovars of R. leguminosarum, but the only polysaccharide mutants described so far for the sequenced strain 3841 are mutants with mutations that affect lipopolysaccharide biosynthesis (1,34). To identify EPS genes in strain 3841, we performed BLAST searches (3) using protein sequences from known polysaccharide biosynthetic genes from different rhizobia.…”
Section: Resultsmentioning
confidence: 99%
“…Previous chemical/genetic studies (48) indicated that QuiNAc was linked to a Kdo residue (Fig. 1), and biosynthetic/ genetic studies (44,45,49,50) provide strong evidence that this Kdo is part of the biosynthetic core of the LPS. It follows from our composition data and these previous conclusions that QuiNAc not only is part of the O antigen but is the first sugar added in O-antigen synthesis.…”
Section: Discussionmentioning
confidence: 99%